SPONTANEOUS RUPTURE OF THE ESOPHAGUS, POSTERIOR PURULENT MEDIASTINITIS, LEFT-SIDED PLEURAL EMPYEMA IN COMBINATION WITH TWO PERFORATED DUODENAL ULCERS, DIFFUSE BILE PERITONITIS, АND RETROPERITONEAL PHLEGMON - A. N. Pogodina; K. M. Rabadanov (Неотложная медицинская помощь)
ABSTRACT. According to most researchers, spontaneous rupture of the esophagus (SRE) occurs relatively rarely, ranging from 1.7% to 17.5% of all cases of damage to the esophagus. Today, there is no one categorical opinion on the effectiveness of various treatments for SRE among surgeons, there are no uniform algorithms for diagnosis and evaluation of the treatment. SRE is a real threat to the life of a patient: SRE mortality rate is up to 75% in the prehospital period and up to 25%-85% in the postoperative period, and depends on the time interval between the rupture of the esophageal wall and the surgery, as well as complications.